FACTORS INFLUENCING STUDENTS’ SPEAKING DIFFICULTIES IN GIVING ORAL PRESENTATION - Riftriani, Ayu Zulfa; Ikhsanudin, Ikhsanudin; Rezeki, Yanti Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
is needed to perform a conversation.The writer observed and found that the students of SMP Negeri 7 Sungai Raya, tended to be difficulties in speaking when oral presentation occurred. She chose to remain silent rather than participating in an oral presentation. This study aimed to investigate the factors for students? speaking difficulties in the classroom using the case study method. The participant was 1 student of the eighth-grade student. The participant was chosen by the characteristics of difficulties in speaking such as tending to be silence in the classroom and the student always use the mother tongue to speak. Using direct observation and semi-structured interview, the study found that the main factors of students? difficulties in speaking were lack of confidence, fear of making mistakes, shyness, and the environment. Based on the findings, it showed that internal and external factors had a great influence on students? speaking difficulties in giving oral presentation. Keywords: Factors, Pontianak,    2016The Researcher, Emi Irwanti____NIM. F12112047 Speaking Difficulties, Oral PresentationAbstractSpeaking is one of the abilities that is needed to perform a conversation.The writer observed and found that the students of SMP Negeri 7 Sungai Raya, tended to be difficulties in speaking when oral presentation occurred. She chose to remain silent rather than participating in an oral presentation. This study aimed to investigate the factors for students? speaking difficulties in the classroom using the case study method. The participant was 1 student of the eighth-grade student. The participant was chosen by the characteristics of difficulties in speaking such as tending to be silence in the classroom and the student always use the mother tongue to speak. Using direct observation and semi-structured interview, the study found that the main factors of students? difficulties in speaking were lack of confidence, fear of making mistakes, shyness, and the environment. Based on the findings, it showed that internal and external factors had a great influence on students? speaking difficulties in giving oral presentation. Keywords: Factors, Pontianak,    2016The Researcher, Emi Irwanti____NIM. F12112047 Speaking Difficulties, Oral Presentation